Between Emotion, Politics and Law: Narrative Transformation and Authoritarian Deliberation in a Land Dispute-triggered Social Drama in China. (18th March 2021) - Liang, Limin
Abstract: Through studying a revenge murder triggered by a land dispute in China and the subsequent trial, this article explores "narrative transformation" in a social drama and proposes an event-based model for authoritarian deliberation. It argues that an obscure murder rose to prominence because it came to be narrated as a different kind of story. Initially viewed as "a normal killing, " it was transformed to represent a "contest" between a law-and-order frame, which emphasizes individual guilt, and a righteous-revenge frame, which symbolizes wider conflicts. The article also contends that in the absence of an institutionalized issue forum, contentious events present a model for authoritarian deliberation. That is to say, deliberation is often pegged to social dramas on the "judicial periphery, " thanks to a liminal phase inviting reflexivity, and exposes elite dissent that is otherwise veiled by an interest-driven alliance. In this case study, the media engaged with other institutions in contentious performances that affirmed hidden social fault-lines but also encouraged deliberation.